ANALISIS KANDUNGAN ADF DAN NDF LIMBAH TIGA VARIETAS TANAMAN SORGUM (Sorghum bicolor Moench) SEBAGAI SUMBER PAKAN UNTUK TERNAK RUMINANSIA - Irine Ike Praptiwi (Universitas Musamus, Merauke, Papua, 2011)
This research aims to (1) optimize the availability of feed through the use of byproduct of Sorghum, (2) analyze the content byproduct of Sorghum as ruminants feed, (3) find and compare the quality and quantity of some varieties of byproduct of Sorghum grown in Merauke regency. The research was conducted in the Semangga District of Merauke regency, Papua province. The samples of leaves of three varieties of sorghum were taken by 7 repetition. The methods used were content of ADF and NDF with Van Soest. The data were analyzed by using statistic analysis with SPSS program. The results revealed that byproduct of sorghum is potential as the source of ruminants feed to optimize the availability of forage. The carrying capacity was 1,23 AU/ha. Numbu variety indicates a better results in which the contents of NDF and ADF are higher but they still in accordance with the ruminants. NDF and ADF of Numbu variety (76,89% and 44,87%) significantly increased (P<0,05) was compare to the other variety, but variety Hegari genjah (73,08% and 41,8%) and variety Kawali (72,85% dan 41,38%) decreased (p>0,05).